Internal Extensions: A Case for The Reassessment of the Architectural Phenomenon of Greenhouse - Ognjen Šukalo; Maja Milić Aleksić; Slobodan Peulić (AGG+)
Glasshouses, greenhouses, conservatories and orangeries – all types of buildings intended specifically for plant cultivation – represent a relatively recent addition to the histories and repertoires of horticulture, agriculture and architecture. During approximately three centuries of their notable existence, these structures managed to not only enable the growth of exotic plants removed far from their natural range but also to form a particular genre of architecture, which developed through different phases, from feeble experiment through high exclusivity to near irrelevance – and back into new paradigms of vegetation-culture-architecture relationship. Starting not only from historical/contemporary examples but also from the general promise of enclosed ecologies, this paper aims both to analyse the phenomenon of greenhouse, as well as to explore parameters and options for its further expansion along conceptual and design-oriented lines.